Integrating Cybersecurity Best Practices in DevOps Pipelines for Securing Distributed Systems - Manikyala, Aditya; Kommineni, Hari Priya; Allam, Abhishekar Reddy; Nizamuddin, Md.; Sridharlakshmi, Narayana Reddy Bommu (ABC Journal of Advanced Research, 2023)
This research examines how DevOps pipelines might improve distributed system security by incorporating cybersecurity best practices. The main goals are to find effective security solutions that can be integrated into the software development lifecycle and to evaluate their influence on agile vulnerability reduction. The study synthesizes literature and industry practices to highlight major conclusions via secondary data review. Early integration of security practices, security testing automation, and a security-first culture are essential for integrating cybersecurity into DevOps operations. The research also emphasizes constant monitoring and incident response to reduce security vulnerabilities. Policy recommendations include adaptive cybersecurity frameworks encouraging automated security procedures and cross-functional cooperation between development, operations, and security teams. Additionally, regulatory agencies should give explicit rules targeted to DevOps concerns. These tips help firms resist emerging cyber threats while preserving DevOps agility and speed. This holistic strategy helps firms secure sensitive data and maintain user and stakeholder confidence in a changing digital context.